Temporal Monitoring of Monsoon Crop Using MODIS 16 Days Composite NDVI Data for Food Security - Sarker, MH; Uddin, MH; Ali, MS; Akhand, MR; Rahman, SMM (Journal of Environmental Science and Natural Resources, 2015)
Bangladesh is an agricultural country and rice is our main crop. It has three types namely Aus, Aman and Boro. The area of Aman is (52.46%) higher than that of Boro (36.43%) and remaining are Aus. SPARRSO has been successfully monitored Aman and Boro rice for last two decades. Due to less percentage of Aus rice (Monsoon crop) area and planting time mostly in monsoon period no one has monitored it regularly. But accurate and timely information on Aus growth and their acreages are essential for strengthening countries food security. Conventional methods of collecting this information are relatively costly and time consuming. Contrarily, satellite observation with its unique capability to observe the earth's surface repeatedly over large area offers a potential means for country scale monitoring of crop condition. The optical remote sensing NOAA, Terra/Aqua, SPOT, Landsat images are not so enough for temporal monitoring of Aus rice due to cloud cover in monsoon period. RADARSAT data is very much useful for such purpose but data is not available as it is very expensive. So study of Aus rice monitoring using MODIS, 16-days composite, NDVI images at 250 m resolution may effectively use for such purpose. The study reveals that about 263011 hectare areas have been found in Barisal region under Aus rice cultivation in 2010. J. Environ. Sci. & Natural Resources, 8(1): 147-152 2015